A novel cross-linked nanocomposite solid-state electrolyte with super flexibility and performance for lithium metal battery. (May 2020) - Tang, Shun; Lan, Qian; Xu, Lin; Liang, Jiyuan; Lou, Ping; Liu, Cui; Mai, Liqiang; Cao, Yuan-Cheng; Cheng, Shijie
Abstract: Solid-state electrolyte batteries are considered as one of the promising next generation power sources. A novel cross-linked nanocomposite polymer electrolyte (CNPE) based on poly (propylene oxide)-poly (ethylene oxide)-poly (propylene oxide) triblock main chains and surface-modified SiO2 nanoparticles are prepared to establish a super flexible and stable polymer framework. The CNPE exhibits high ionic conductivity of 1.32 mS cm −1 at 20 °C and its electrochemical stability window reaches up to 6.5 V ( versus Li + /Li). The favorable Li deposition behavior provided by CNPE films is identified by the stripping/plating test at a current density of 2.4 mA cm −2 for 1700 h. The CNPE films possess excellent mechanical stability (highly stretchable with ultimate elongation of 700%). Li/CNPE/LiFePO4 batteries deliver an initial discharge capacity of 160 mAh g −1 at 0.2 C, which is 94.1% of the theoretic capacity, and maintain the high specific capacity of 148 mAh g −1 at 0.5 C. This work provides a new approach toward designing high performance electrolyte for lithium metal batteries. Graphical abstract: Image 1 Highlights: This hybrid polymer electrolyte combines the advantages of the hydrogen bonding system and nanocomposite framework. The electrolyte membranes exhibit excellent mechanical stability and super flexibility. The Li/Li symmetric cells with this electrolyte display remarkable Li stripping/plating behavior. The LiFePO4 /Li cells with this electrolyte exhibit superior rate performance and cycling stability.